2011
DOI: 10.1158/1055-9965.epi-11-0459
|View full text |Cite
|
Sign up to set email alerts
|

Stage at Diagnosis and Comorbidity Influence Breast Cancer Survival in First Nations Women in Ontario, Canada

Abstract: Background: Indigenous populations in Canada and abroad have poorer survival after a breast cancer diagnosis compared with their geographic counterparts; however, the influence of many demographic, personal, tumor, and treatment factors has not been examined to describe this disparity according to stage at diagnosis.Methods: A case-case design was employed to compare First Nations (FN) women (n ¼ 287) to a frequencymatched random sample of non-FN women (n ¼ 671) diagnosed with breast cancer within the Ontario … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
(22 reference statements)
0
31
0
1
Order By: Relevance
“…In part, this is a consequence of how studies are indexed. We consider this point more fully in the discussion, but for now it bears noting that one Canadian study [117] that included attention to differences in receipt of treatment between First Nations and non-First Nations women was not included in this review as it was not indexed nor did it use text word terms for 'health services accessibility' or 'healthcare disparities' (the emphasis was on differences rather than disparities).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…In part, this is a consequence of how studies are indexed. We consider this point more fully in the discussion, but for now it bears noting that one Canadian study [117] that included attention to differences in receipt of treatment between First Nations and non-First Nations women was not included in this review as it was not indexed nor did it use text word terms for 'health services accessibility' or 'healthcare disparities' (the emphasis was on differences rather than disparities).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Many studies have reported that comorbidity at/around the time of diagnosis, most often measured by a comorbidity index, such as the Charlson Comorbidity Index (CCI), or simple additive summary scores for number of comorbidities, predicts poorer survival among breast cancer patients [6, 8, 1119]. However, the influence of individual comorbidities on prognosis may vary, and these summary measures may provide limited information [5, 10, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy for Manitoba Métis people has been reported as 5 to 6 years lower than that of the general population [9-12]. As well, diabetes prevalence is elevated for the Métis compared to the rest of the population, with reports of up to twice the prevalence in Western Canada [10,13-16].…”
Section: Introductionmentioning
confidence: 99%